Biofilm forming ability and time course study of growth of Salmonella Typhi on fresh produce surfaces - Tang, Poh Li; Pui, Chai Fung; Wong, Woan Chwen; Ahmad, Noorlis; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
This study aimed to determine the biofilm formation ability by Salmonella Typhi on cucumber, mango and guava surface, as well as to determine the relationship between time contact and biofilm formation. Crystal violet assay was performed to quantify the biofilm formation based on the value of optical density at 570 nm of the destaining crystal violet at the specific interval time. The result showed that the attachment of the bacterial cells on the fresh produce surface increased with the contact time. The readings of OD 570 at time 12 h for cucumber, mango and guava surfaces were 0.824, 0.683 and 0.598, respectively, indicating that the biofilm formation by Salmonella Typhi on different fresh produce surface varied with time. Since the result showed that Salmonella Typhi formed biofilm on fresh produce surfaces, hygienic practice from farm to fork including handling, processing, distribution and storage of the fresh produce should be of concern.